The Dementia Early Stage Cognitive Aids New Trial (DESCANT) intervention: A goal attainment scaling approach to promote self‐management. (15th December 2020) - Chester, Helen; Beresford, Rebecca; Clarkson, Paul; Entwistle, Charlotte; Gillan, Vincent; Hughes, Jane; Orrell, Martin; Pitts, Rosa; Russell, Ian; Symonds, Eileen; Challis, David; ,
Abstract: Objectives: This study investigated goals identified by people with dementia and their carers to promote the self‐management of symptoms and abilities; measured achievement using goal attainment scaling (GAS); and explored the reflections of Dementia Support Practitioners (DSPs) facilitating it. Methods and design: Within this pragmatic randomised trial, DSPs gave memory aids, training and support to people with mild to moderate dementia and their carers at home. Data were collected across seven NHS Trusts in England and Wales (2016–2018) and abstracted from intervention records and semi‐structured interviews with DSPs delivering the intervention, supplemented by a subset of the trial dataset. Measures were created to permit quantification and descriptive analysis and interview data thematically analysed. A GAS measure for this intervention in this client group was derived. Results: Engagement was high across the 117 participants and 293 goals were identified. These reflected individual circumstances and needs and enabled classification and assessment of their attainment. Seventeen goal types were identified across six domains: self‐care, household tasks, daily occupation, orientation, communication, and well‐being and safety. On average participants achieved nominally significant improvement regarding the specified goals of 1.4 with standard deviation of 0.6. Five interviews suggested that DSPs' experiences of goal setting were also positive. Conclusions: GAS is useful for assessing psychosocial interventions for people with early‐stage dementia. It has a utility in identifying goals, promoting self‐management and providing a personalised outcome measure. There is a strong case for exploring whether these clear benefits translate to other interventions in other populations in other places.